2013
DOI: 10.1093/eurheartj/eht390
|View full text |Cite
|
Sign up to set email alerts
|

Should axis deviation or atrial enlargement be categorised as abnormal in young athletes? The athlete's electrocardiogram: time for re-appraisal of markers of pathology

Abstract: Isolated axis deviation and atrial enlargement comprise a high burden of Group 2 changes in athletes and do not predict underlying structural cardiac disease. Exclusion of these anomalies from current ESC guidelines would improve specificity and cost-effectiveness of pre-participation screening with ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 18 publications
1
57
0
1
Order By: Relevance
“…On the basis of our long-standing experience of evaluating several thousand athletes and in line with recent consensus documents and research findings, 7,12,14,15,17,19,20,26 we identified certain ECG anomalies (borderline variants; Figure 1A) currently included in the group 2 category of the ESC recommendations and some deemed abnormal by the Seattle criteria that we would now consider normal variants in asymptomatic athletes without a relevant family history or abnormal cardiac examination. Specifically, we would not recommend further investigation of athletes with any one of the following ECG patterns when present either in isolation or in association with recognized training-related ECG changes: (1) left atrial enlargement, (2) right atrial enlargement, (3) left axis deviation, (4) right axis deviation, and (5) Sokolow-Lyon voltage criteria for right ventricular hypertrophy.…”
Section: Refined Ecg Criteriasupporting
confidence: 57%
See 3 more Smart Citations
“…On the basis of our long-standing experience of evaluating several thousand athletes and in line with recent consensus documents and research findings, 7,12,14,15,17,19,20,26 we identified certain ECG anomalies (borderline variants; Figure 1A) currently included in the group 2 category of the ESC recommendations and some deemed abnormal by the Seattle criteria that we would now consider normal variants in asymptomatic athletes without a relevant family history or abnormal cardiac examination. Specifically, we would not recommend further investigation of athletes with any one of the following ECG patterns when present either in isolation or in association with recognized training-related ECG changes: (1) left atrial enlargement, (2) right atrial enlargement, (3) left axis deviation, (4) right axis deviation, and (5) Sokolow-Lyon voltage criteria for right ventricular hypertrophy.…”
Section: Refined Ecg Criteriasupporting
confidence: 57%
“…13 New data based on large athlete cohorts from our group have revealed several isolated ECG patterns to have a low diagnostic yield for cardiac disease, questioning their relevance as markers of pathology in elite athletes. 14,15 Current guidelines in practice are consensus based and do not fully incorporate such scientific observations in their recommendations. Furthermore, they are derived almost exclusively from unselected white athletes (WAs) 16 and have not been evaluated in large cohorts of elite athletes of African/Afro-Caribbean origin (black athletes; BAs).…”
Section: Editorial See P 1626 Clinical Perspective On P 1649mentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 19 athletes presented only one borderline change and therefore did not necessitate any further cardiological work-up. What is worth noticing, in our young population none of the sportsmen examined fulfilled the criteria of left atrial enlargement (LAE), which was postulated as a reason for false positive results of ECG screening in some populations [23]. Surprisingly, the right atrial enlargement (RAE) (which is not perceived as a pathologic finding in the Seattle criteria) was present in seven individuals.…”
Section: Discussionmentioning
confidence: 79%